WEED DIVERSITY AND DOMINANCE IN SMALLHOLDER MATURE RUBBER PLANTATIONS - Sari, Resti Puspa Kartika; Pujisiswanto, Hidayat; Permatasari, Nindy; Fauziah, Lu'lu' Kholidah (Universitas Gunadarma, 2024)
One of the obstacles in rubber plant cultivation is the presence of weeds. Weeds reduce the quantity and quality of yields, interfere with the maintenance and harvesting process, and become hosts for pests and plant diseases. This study aims to determine the diversity and dominance of weeds in smallholder rubber plantations. The research was conducted in two locations of smallholder rubber plantations in Juni-Juli 2023. The first location was in Natar, South Lampung and the second location was in Negeri Katon, Pesawaran. Sample selection was done by purposive sampling method with 4 replicates. The results showed that in the Natar location there were 13 weed species, while in the Negeri Katon location there were 14 weed species. Three weed species that dominated in the two locations were Axonopus compressus, Asystasia gangetica, and Ottochloa nodosa. The A. compressus weed had the highest SDR in both locations at 20.23% in the Natar location and 18.79% in the Negeri Katon location. The results of this study can be used as a basis for determining appropriate weed control techniques.